The Relationship Between Specific Nutritional Interventions for Breastfeeding Mothers and Toddlers and Stunting in Toddlers at Banjarsari Community Health Center - Riska Triyunita; Yuliawati Yuliawati; Rofana Aghniya (Jurnal Maternitas Kebidanan, 2026)
Stunting is a condition in which children under five years old (toddlers) cannot grow due to chronic malnutrition, causing the child to be shorter than their age. Based on 2024 data, stunted toddlers in the world were 23.2%, in Indonesia 19.8%, in Lampung Province 13.1%, in Metro City 12.1%, in 2023 at Banjarsari Health Center 6.08%. Stunting causes a 4.56-fold decrease in IQ compared to non-stunted children, stunted children are likely to have a non-verbal IQ below 89, so the government issued specific nutritional interventions, one of which is for breastfeeding mothers. The purpose of this study was to determine the relationship between specific nutritional interventions for breastfeeding mothers and toddlers with stunted toddlers at Banjarsari Health Center. This type of research is quantitative with a case-control design. The population of all toddlers at Banjarsari Health Center is 622 toddlers. The sample size was determined based on the Sastroasmoro formula, obtaining 66 respondents. The sampling technique used stratified random sampling. Data collection was conducted using height measurements, observation, interviews, and documentation using a checklist and stadiometer. Data were analyzed univariately and bivariately using chi-square. The results of the study from 66 respondents showed that the proportion of specific nutritional interventions for breastfeeding mothers and infants from birth to 6 months was 87.9%, and the proportion of specific nutritional interventions for breastfeeding mothers and children aged 7-23 months was 92.1%. Based on the analysis, the p-value for specific nutritional interventions for breastfeeding mothers and infants from birth to 6 months was (p=0.014 OR=7.8) and specific nutritional interventions for breastfeeding mothers and children aged 7-23 months were (p=0.039, 0R=9.5). The conclusion from the results of the study at the Banjarsari Community Health Center in 2025 was that there was a significant relationship between specific nutritional interventions for breastfeeding mothers and stunted toddlers. Efforts to prevent and overcome stunting should be carried out through the active involvement of health workers together with Posyandu cadres and intensive assistance for breastfeeding mothers. Improvement of nutritional counseling services also needs to be optimized with a flexible schedule and a personal approach, including through home visits. These efforts must be supported by cross-sector collaboration, increased access to health services, and the use of digital media to disseminate nutrition information widely and facilitate communication between mothers and health workers.